PENGARUH FAKTOR-FAKTOR OPERASIONAL TERHADAP KINERJA FINANSIAL DIMEDIASI OLEH KEPUASAN PELANGGAN - Mutiara, Nabila; Santosa, Wahyuningsih; Darasih, Ratna; Fortuna, Desca (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Intense business competition and dynamic environments challenge construction firms to sustain financial performance through effective operational management. This study examines the influence of supplier performance, innovation and learning, and operational performance on financial performance mediated by customer satisfaction in West Jakarta construction companies. Quantitative research with causal design was conducted using purposive sampling of 175 employees and managers, surveyed via a 5-point Likert scale questionnaire. Data analysis employed SPSS for descriptives and AMOS for Structural Equation Modeling to test direct and mediation effects. Results reveal supplier performance significantly affects innovation-learning, operational performance, and customer satisfaction but not directly financial performance. Innovation-learning positively influences all variables including financial performance, while operational performance impacts only customer satisfaction. Customer satisfaction fully mediates the relationship between all three operational factors and financial performance, with all variables showing positive perceptions (means >3.79). In conclusion, customer satisfaction serves as the critical mechanism linking operational excellence to financial success, emphasizing customer-centric strategies over internal efficiency alone.